POLA ASUH ORANG TUA SISWA TERHADAP INTERAKSI SOSIAL SISWA (STUDI KASUS DI MIN 2 KOTA TASIKMALAYA) - Zakiyah, Suci (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
In raising and educating children, every parent certainly wants the best for their children. This desire will later shape the parenting style that parents will instill in their children. To be accepted and able to blend into society generally depends on the parenting style that parents apply in developing social interactions in their children. The problems in this research are children who do not interact enough with their peers, there are children who are hyper active and noisy in class, there are children who always want the teacher to pay attention and there are even children who are often bullied because their appearance and abilities are not equal to their friends. other. This research uses a qualitative approach. The results of this research concluded that parental parenting at home is a factor that a child needs to form character or personality, while social interaction with peers is a form of interaction to control their emotions.